2006
DOI: 10.1159/000092532
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Ole e 9 Allergen in Olive Pollen Extracts: Relevance of Minor Allergens in Immunotherapy Treatments

Abstract: Background: Clustered severe adverse reactions to immunotherapy with olive pollen extracts have been occasionally reported in areas where olive trees are extensively grown. Allergic patients from these areas, in addition to the major olive pollen allergen Ole e 1, frequently recognize a recently described allergen, Ole e 9. Objective: We aimed to develop an immunoassay to measure Ole e 9 concentration and to study the variability of this allergen in olive pollen extracts. Methods: Monoclonal antibodies (mAb) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Of course, for the moment, these remain mainly theoretical considerations; significant limitations include incomplete and sometimes conflicting published data, inadequate information about the allergen content of commercial SIT extracts as well as reported qualitative and quantitative variability between different SIT products and manufacturers [12,31,86,87,88]. In addition, taking into account the limited number of allergen components currently available for clinical use and the fact that exact matching of natural SIT extracts to individual sensitization profiles may probably be a Utopian goal, one could reasonably argue against the practical value of such an attempt.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, for the moment, these remain mainly theoretical considerations; significant limitations include incomplete and sometimes conflicting published data, inadequate information about the allergen content of commercial SIT extracts as well as reported qualitative and quantitative variability between different SIT products and manufacturers [12,31,86,87,88]. In addition, taking into account the limited number of allergen components currently available for clinical use and the fact that exact matching of natural SIT extracts to individual sensitization profiles may probably be a Utopian goal, one could reasonably argue against the practical value of such an attempt.…”
Section: Resultsmentioning
confidence: 99%
“…The minor olive allergen Ole e 3, a calcium-binding protein/polcalcin, is a pan-allergenic structure and homologues have been described in ash and lilac [24,25,26]. The β-1,3-glucanase Ole e 9 is a major allergen, and although respective allergens have not been identified in the remaining Oleaceae species, cross-reactive structures have been detected in ash, lilac and privet [27,28,29]. According to one reference [30], a 11-kDa allergen, named Ole e 10 by the authors, has been identified as glycosyl transferase.…”
Section: Tree Pollenmentioning
confidence: 99%
“…To date, 10 allergens from olive pollen, Ole e 1-Ole e 10, have been characterized (Rodríguez et al 2002;Barral et al 2004), but only the three-dimensional (3D) structure of Ole e 6 has been determined (Treviño et al 2004). Among them, Ole e 9 is important because it has been described as a potential cause of adverse reactions in specific immunotherapy (SIT) (Duffort et al 2006). Ole e 9 is composed of two structurally and immunologically independent domains: N-and C-terminal domains (NtD and CtD, 36 kDa and 10 kDa, respectively), which can be separately produced by recombinant DNA technology (Palomares et al 2003(Palomares et al , 2005.…”
mentioning
confidence: 99%